Major factors controlling fracture development in the Middle Permian Lucaogou Formation tight oil reservoir, Junggar Basin, NW China. (15th September 2017) - Zhang, Chen; Zhu, Deyu; Luo, Qun; Liu, Luofu; Liu, Dongdong; Yan, Lin; Zhang, Yunzhao
Graphical abstract: Highlights: Characteristics of macro-fractures and micro-fractures in the Lucaogou Formation are described. The study also shows that major factors that control fractures development in the Lucaogou Formation. Four major periods of fracture formation in the Lucaogou Formation are identified. Tectonic activity is the most important control on fracture generation in the Lucaogou Formation. Abstract: Natural fractures in seven wells from the Middle Permian Lucaogou Formation in the Junggar Basin were evaluated in light of regional structural evolution, tight reservoir geochemistry (including TOC and mineral composition), carbon and oxygen isotopes of calcite-filled fractures, and acoustic emission (AE). Factors controlling the development of natural fractures were analyzed using qualitative and/or semi-quantitative techniques, with results showing that tectonic factors are the primary control on fracture development in the Middle Permian Lucaogou Formation of the Junggar Basin. Analyses of calcite, dolomite, and TOC show positive correlations with the number of fractures, while deltaic lithofacies appear to be the most favorable for fracture development. Mineral content was found to be a major control on tectonic fracture development, while TOC content and sedimentary facies mainly control bedding fractures. Carbon and oxygen isotopes vary greatly in calcite-filled fractures (δ 13 C ranges from 0.87‰ to 7.98‰, while δ 18 O ranges from −12.63‰ to −5.65‰), indicating that fracture development increases with intensified tectonic activity or enhanced diagenetic alteration. By analyzing the cross-cutting relationships of fractures in core, as well as four Kaiser Effect points in the acoustic emission curve, we observed four stages of tectonic fracture development. First-stage fractures are extensional, and were generated in the late Triassic, with calcite fracture fills formed between 36.51 °C and 56.89 °C. Second-stage fractures are shear fractures caused by extrusion stress from the southwest to the northeast, generated by the rapid uplift of the Tianshan in the Middle and Late Jurassic; calcite fracture fills formed between 62.91 °C and 69.88 °C. Third-stage fractures are NNW-trending shear fractures that resulted from north-south extrusion and thrusting in a foreland depression along the front of the Early Cretaceous Bogda Mountains. Calcite fracture fills formed between 81.74 °C and 85.43 °C. Fourth-stage fractures inherited the tectonic framework of the third stage, resulting in fractures with the same orientation, but without calcite filling. By differentiating the various stages of fracture development, we were able to better understand the origin of fractures in tight oil reservoirs and their significance for exploration and development.